PENENTUAN DOSIS OPTIMUM KOAGULAN PADA PENGOLAHAN AIR BERSIH PERUMDA TIRTA PENGABUAN - Amilla Khairunnisa; Siti Umi Kalsum; Hadrah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The existing condition of clean water treatment at Perumda Tirta Pengabuan does not carry out laboratory tests on the use of chemicals, both coagulants and disinfectants. This causes the exact and optimum dosage in water treatment is not known. For this reason, researchers tested water samples in the laboratory using the jar test method with four variations of chemicals, namely aluminum sulfate or alum (Al2(SO4)3), sucolite, PAC, and soda ash. In addition to variations in chemicals to find out the optimum dose using a variety of doses (1ml, 2ml, 3ml, 4ml, 5ml,) time variations and fast and slow stirring (100 rpm 1 minute – reduced 20 rpm 15 minutes, 160 rpm 1 minute – 40 rpm 4 minutes, 200 rpm 1 minute – 50 rpm 10 minutes). From the results of research on the raw water quality of the Pengabuan River at high tide when it rains it is 42.31 NTU with a pH of 6.18, when it is not raining it is 33.75 NTU with a pH of 6.16, and when it rains ebb the turbidity results obtained are 58.69 NTU with a pH of 6.25 and receding when it doesn't rain 29.43 NTU with a pH of 6.28, where these results do not meet the quality standard. The use of chemicals that are effective in reducing turbidity concentration (NTU) is PAC from the chemical alum (Al2(SO4)3), and sucolite. The optimum dose of PAC with the value interval from lowest to highest is 1-3 ml with conditions during high tide when it rains < low tide does not rain and rain < high tide does not rain.